Perancangan Sistem Informasi Pembayaran SPP TPA Islam Menggunakan Metode Waterfall - Rizki, Rizki Ridwan (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
Technology, especially in the information sector, is currently increasingly developing and many companies and institutions, including those in the education sector, are using information technology. Apart from that, there are still schools that do not use computer technology, including Islamic TPA. This school requires computer processing of tuition payment reports due to the large number of books needed to manage payments. Therefore, the use of computers is expected to overcome the administrative problems of Islamic TPA schools.